Smart Emergency Detection Framework by IR4.0 for Safety Management among G7 Contractors: A Pilot Study - Kasim, Narimah Binti; Razali, Sali Amirah; Md Ariffin, Khadijah (International Journal of Sustainable Construction Engineering and Technology, 2022)
The Industrial Revolution 4.0 were positively demanded towards the direction of Construction 4.0 in Malaysia. In realizing the IR 4.0 technology towards Construction 4.0, the new mechanism known as Smart Emergency Detection Framework was developed to enhance the safety management at the construction site. Smart Emergency Detection Framework is the guideline reference to assist construction players in safety management that integrated with IR 4.0 technology for early emergency detection and potential hazard. The objectives of this research are the objectives are to evaluate the technical and navigational aspects of the online survey procedure and the instrument itself, and to validate the pilot study questionnaire. This study creates a new questionnaire with the goal of purposing the Smart Emergency Detection Framework. Content validity and linguistic analysis were carried out before the completion of the pilot study questionnaire. Then, the Google Form questionnaire was distributed via WhatsApp and email. Total of 32 respondents were obtained for the pilot study, after further finalize only 30 respondents were selected due to uncompleted responds. Based on the findings, the overall value of Cronbach Alpha for 112 items was 0.996, indicating a range of strong internal consistency that was reliable for the pilot study. In the context, all respondents were able to answer the research question and all the relevant element that concerning the respondent’s feedback were identified. In conclusion, the pilot study assessment results will be based for additional clarification and improvement of the questionnaires before major data collection.